Teacher training colleges in wrong 'place' - Abd Razak, Dzulkifli (2009)
AS Malaysia looks for a new economic model to enable it to become a highincome country, it is inevitable that the current education system must be reviewed, if not changed. Time and time again, history has shown that economic and education systems change in tandem with one another. More frequently, education leads the way for a new economic model. Thus, the current education system that resembles an assembly line has outlived its usefulness in trying to spur the future economic system which is largely based on creativity and innovation. And worse, if we are seeking a more sustainable economic model inspired by creative knowledge and technologies.